Population Genomics Training for the Next Generation of Conservation Geneticists: ConGen 2018 Workshop. (10th March 2020) - Stahlke, Amanda; Bell, Donavan; Dhendup, Tashi; Kern, Brooke; Pannoni, Samuel; Robinson, Zachary; Strait, Jeffrey; Smith, Seth; Hand, Brian K; Hohenlohe, Paul A; Luikart, Gordon
Abstract: The increasing availability and complexity of next-generation sequencing (NGS) data sets make ongoing training an essential component of conservation and population genetics research. A workshop entitled "ConGen 2018" was recently held to train researchers in conceptual and practical aspects of NGS data production and analysis for conservation and ecological applications. Sixteen instructors provided helpful lectures, discussions, and hands-on exercises regarding how to plan, produce, and analyze data for many important research questions. Lecture topics ranged from understanding probabilistic (e.g., Bayesian) genotype calling to the detection of local adaptation signatures from genomic, transcriptomic, and epigenomic data. We report on progress in addressing central questions of conservation genomics, advances in NGS data analysis, the potential for genomic tools to assess adaptive capacity, and strategies for training the next generation of conservation genomicists.